Help with this question please1
![Help with this question please1 class=](https://us-static.z-dn.net/files/dba/b57ba5463a56fac1c2185132c658e126.png)
Answer:
(-2,8)
Step-by-step explanation:
3x+3y = 18
2x+y = 4
Multiply the second equation by -3
-3(2x+y) = -3*4
-6x-3y = -12
Add this to the first equation
3x+3y = 18
-6x-3y = -12
-------------------------
-3x = 6
Divide each side by -3
-3x/-3 = 6/-3
x = -2
Now solve for y
2x+y = 4
2(-2) +y = 4
-4+y =4
Add 4 to each side
-4+4+y = 4+4
y =8
Answer:
(-2,8)
Step-by-step explanation:
3x + 3y = 18 (1)
2x + y = 4 (2)
(1) - 3(2)
3x + 3y = 18
-(6x + 3y = 12)
-3x = 6
x = -2
Using (2)
2(-2) + y = 4
-4 + y = 4
y = 8